PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BESMINDO MATERI SEWATAMA DURI-RIAU - Aritonang, Anggita Evasari; Purba, Betniar (LPPM Universitas Katolik Santo Thomas Medan, 2023)
The purpose of this study was to determine the effect of Occupational Safety and Health on Employee Performance at PT. Besmindo Materials Sewatama Duri-Riau. Data collection was carried out by distributing questionnaires which were given to 81 floorman employees. Data analysis in this study used the SPSS Version 22 application. The results of this assessment indicate that the Occupational Safety and Health variables simultaneously have a positive and significant effect on Employee Performance at PT. Besmindo Materials Sewatama Duri-Riau. While partially shows that “Work Safety has a positive and significant effect on Employee Performance at PT. Besmindo Material Sewatama Duri-Riau with a multiple regression coefficient value of 0.426 and a significant value of 0.001 <0.05 (smaller than the error tolerance value). Occupational Health has a positive and significant effect on Employee Performance at PT. Besmindo Materials Sewatama Duri-Riau with a regression coefficient of 0.452 and a significant value of 0.007<0.05 (smaller than the error value). From the results of the research and also the discussion conducted, PT. Besmindo Materials Sewatama Duri-Riau to further develop and pay attention to the indicators contained in Occupational Safety and Occupational Health on Employee Performance at PT. Besmindo Materials Sewatama Duri-Riau.